Znaczenie Dunaju w europejskiej sieci dróg wodnych (Politeja, 2020)
The Role of the Danube River in the Trans-European Waterway NetworkIn the 20th century, the Danube Region was subject to numerous and far-reaching political transformations, which had a negative impact on the expansion of the Danube waterway transport, affected mainly by political, economical and military crises that took place in the 1990s. Nowadays, only 9% of all river cargo is shipped via the Danube River. The European Union makes an effort to increase this number up to 30%, and to ensure the river’s permanent inclusion in the Trans-European Transport Network, with an ongoing process of adjusting the Danube shipping law to the regulations applicable to other European rivers. Nonetheless, the implementation of the EU Strategy for the Danube Region has little effect on the transportation growth in the Danube Basin so far – due to insufficient support from the European Union, the Danubian countries’ unwillingness to carry out expensive investments, and difficulties related to the process of redirecting the existing trade routes.